Effect of Ply Thickness on The Bearing Capacity of Bolted-Fiber Cemboard: Numerical Modelling Using FEM - Ismail, N. N.; Jaini, Z. M. (Recent Trends in Civil Engineering and Built Environment, 2021)
Fiber cemboard is one of the most important materials used in the construction of buildings. The application of fiber cemboard has led to the pre-fabricated and build-up system known as bolted-fiber cemboard to be used as floor system. Therefore, this study aims to numerically investigate the bearing capacity and slip-displacement of bolted-fiber cemboard. The numerical modelling involves two-ply fiber cemboard with size 210 mm length, 210 mm width and various thicknesses ranging from 9 mm to 20 mm. The bolted-fiber cemboard under push-out test was modeled in WELSIM. The results of stress-forces curves and stress-displacement curves were obtained. It was found that the higher the thickness of fiber cemboard, the higher the bearing capacity. The thicker fiber cemboard used does provide better performance of bearing capacity but it could lead to higher-slip displacement due to higher rate of damage. Overall, the final result of this study shows that bolted-fiber cemboard has a good potential as a structural member due to the excellent serviceability.